2022
DOI: 10.4317/medoral.25259
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations in SARS-CoV-2 infection

Abstract: Background We aimed to evaluate the prevalence of predisposing factors and oral manifestations in SARS-CoV-2 infection. Material and Methods 204 SARS-CoV-2 positive patients were included in the study. Questions regarding the systemic, periodontal health, oral hygiene habits, common symptoms and, oral manifestations of COVID-19 such as oral lesions, and dry mouth were included in the survey. The Visual Analogue Scale (VAS) was used. Results 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 30 publications
0
18
0
6
Order By: Relevance
“…Italy accounted for the most articles, with 14 studies [ 16 , 19 , 20 , 22 , 23 , 28 , 29 , 36 , 37 , 58 , 66 , 72 , 81 , 86 ]. This was followed by India with 8 studies [ 17 , 33 , 44 , 45 , 50 , 55 , 80 , 83 ], United States with 7 studies [ 21 , 25 ,, 30 , 31 , 54 , 62 , 79 ], Brazil with 7 studies [ 9 , 47 , 49 , 52 , 56 , 75 , 77 ], and both Egypt and Turkey with 5 studies each [ 34 , 38 , 41 , 68 , 71 ] and [ 26 , 39 , 42 , 48 , 64 ], respectively. Iran [ 5 , 53 , 59 , 60 ], Iraq [ 12 , 43 , ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Italy accounted for the most articles, with 14 studies [ 16 , 19 , 20 , 22 , 23 , 28 , 29 , 36 , 37 , 58 , 66 , 72 , 81 , 86 ]. This was followed by India with 8 studies [ 17 , 33 , 44 , 45 , 50 , 55 , 80 , 83 ], United States with 7 studies [ 21 , 25 ,, 30 , 31 , 54 , 62 , 79 ], Brazil with 7 studies [ 9 , 47 , 49 , 52 , 56 , 75 , 77 ], and both Egypt and Turkey with 5 studies each [ 34 , 38 , 41 , 68 , 71 ] and [ 26 , 39 , 42 , 48 , 64 ], respectively. Iran [ 5 , 53 , 59 , 60 ], Iraq [ 12 , 43 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Most of the 79 studies were cross-sectional studies ( n =41) [ 5 , 12 26 , 29 31 , 33 , 34 , 37 46 , 48 51 , 53 55 , 84 − 86 ] followed by case reports ( n =20) [ 9 , 61 75 , 78 − 81 ], case series ( n =11) [ 6 , 8 , 56 60 , 76 , 77 , 82 , 83 ], retrospective studies ( n =6) [ 27 , 28 , 35 , 36 , 47 , 52 ], and case-control studies ( n =1) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Martín Carreras-Presas et al reported different types of oral mucosal lesions (ulcer, vesicle, bulla, and desquamative gingivitis) in patients with COVID-19 [ 21 ]. Tuter et al showed that dry mouth is the most common and oral ulcers and tongue lesions are the second common oral manifestation in COVID-19 patients [ 13 ]. Cuevas-Gonzalez et al stated that the most common main oral manifestations related to SARS-CoV-2 were dysgeusia, dry mouth, burning mouth, ulcerative lesions, and Candida Albicans infections in their systematic review including a total of 18 studies [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common clinical symptoms include fever, tiredness, headache, sore throat, dyspnea, myalgia, dry cough, abdominal pain, vomiting, and diarrhea. In addition to these primary manifestations, some oral symptoms have also been reported, such as xerostomia, aphthous-like lesions, ulcers, tongue depapillation, necrotizing gingivitis, and taste disorders, including the loss of taste and salivary gland infections ( 2 - 4 ).…”
Section: Introductionmentioning
confidence: 99%